Application of Ultraviolet Light for Poultry Production: A Review of Impacts on Behavior, Physiology, and Production - Rana, Md. Sohel; Campbell, Dana L. M. (Frontiers in Animal Science, 2021)
The application of ultraviolet (UV) light in poultry production is garnering increased interest with the drive towards improved poultry welfare and optimized production. Poultry can see in the UV spectrum (UVA wavelengths: 320-400 nm) thus inclusion of these shorter wavelengths may be viewed as more natural but are typically excluded in conventional artificial lights. Furthermore, UVB wavelengths (280-315) have physiological impact through stimulation of vitamin D pathways that can then improve skeletal health. However, better understanding of the effects of UV supplementation must occur before implementation practically. This non-systematic literature review aimed to summarize the impacts of UV supplementation on the behavior, welfare, and production of laying hens, meat chickens (breeders and growers), and other domestic poultry species including directions for future research. The literature demonstrated that UVA light has positive impacts on reducing fear and stress responses but in some research, it significantly increases feather pecking over age during the production phase. UVB light will significantly improve skeletal health, but an optimum duration of exposure is necessary to get this benefit. Supplementation with UVB light may have more distinct impacts on egg production and eggshell quality when hens are experiencing a dietary vitamin D3 deficiency, or if they are at the terminal end of production. The relative benefits of UVB supplementation across different ages needs to be further verified along with commercial trials to confirm beneficial or detrimental impacts of adding UVA wavelengths. Future research is warranted to determine whether adding natural light wavelengths to indoor poultry production is indeed a positive step towards optimizing commercial housing systems.